(untitled) (The Review of Diabetic Studies, 2025)
Background: Hypothyroidism is a common endocrine disorder characterized by reduced thyroid hormone production and associated metabolic disturbances. In Ayurveda, the condition may be correlated with Dhatwagnimandya and Kapha-dominant metabolic impairment. This case report explores the role of integrative Ayurvedic management in primary hypothyroidism. Case presentation: A 33-year-old male presented with complaints of fatigue, weight gain, and constipation for six months. Laboratory investigations revealed markedly elevated thyroid-stimulating hormone (TSH ≥100 µIU/dL) and reduced thyroxine levels (T4 1.63 µg/dL), confirming hypothyroidism. Intervention:The patient was treated with classical Ayurvedic therapy including Deepana-Pachana, Snehapana with Panchatikta Ghrita, followed by Vamana Karma. Post-detoxification, the patient received oral medication (Tab. Thyronil 500 mg three times daily) for six months. Results:Progressive improvement was observed in clinical symptoms and thyroid function parameters. TSH levels decreased from ≥100 µIU/dL to 8.19 µIU/dL, while T4 improved from 1.63 µg/dL to 6.35 µg/dL during follow-up. Zulewski clinical score reduced from 8 to 0, indicating resolution of hypothyroid symptoms. Conclusion:The integrative Ayurvedic approach involving Vamana Karma followed by herbal medication showed potential benefits in improving clinical and biochemical parameters in hypothyroidism. Further controlled studies are required to validate these findings.